241 Are Patients Really Willing to Undergo Surgery for Peyronie's Disease?. (1st May 2022) - Capogrosso, P; Candela, L; Cazzaniga, W; Costa, A; Fallara, G; Boeri, L; Pozzi, E; Belladelli, F; Schifano, N; Cignoli, D; Dehò, F; Abbate, C; et al.
ABSTRACT: Introduction: There is a current lack of effective conservative treatments for Peyronie Disease (PD). Surgery represents an effective treatment, despite being associated with bothering complications, including erectile dysfunction (ED). Objective: We investigated patients wish of being operated for PD at a single center. Methods: Data were prospectively collected for patients managed for penile curvature because of PD in 2016-2020. Baseline data included age, time from PD onset, penile pain, curvature degree, difficulty at penetration, concomitant hour-glass deformity and ED. All patients were offered conservative treatments, including oral therapy or topical injections regardless of curvature degree. Tunical shortening or lengthening procedures were offered as an alternative to conservative treatments. Penile prosthesis implantation was offered to those with concomitant ED. Patients compliance with surgery was recorded. Logistic regression analyses tested the profile of patients who were more likely to comply with surgery. Results: Data were available for 218 patients. Median(IQR) age was 57(49, 63) yrs and length of PD after onset was 14(3, 28) months. Median curvature was 30°(20, 45); of 218, 8(3.7%) patients had concomitant hour-glass deformity. Pain was complained by 30(14%) patients, while difficulty at penetration and ED were reported by 62(28%) and 87(40%) patients. Of all, 78(32%) patients had been treated with tadalafil OaD; 41(19%) patients received iontophoresis with verapamil; 35(16%) SWT; and, 31(14%) CCH injections. A significant improvement (defined as a curvature reduction≥20°) was reported in 52(24%) cases. Overall, only 59 (27%) patients were willing to eventually undergo surgery for PD. Younger patients (OR:0.95, 95%CI: 0.92, 0.98;p=0.003) and patients with more severe curvatures (OR:1.03; 95%CI: 1.01, 1.04;p=<0.001) were more likely to comply with surgery, after accounting for other clinical variables. According to this model, a man aged 50 yrs with a curvature <20° would accept surgery only in 24% of cases compared to 45% for a same age man with >45° of curvature (Fig1). Conclusions: Compliance to surgery is low among patients with PD, thus further stressing the urgent need for effective conservative treatments. Surgery should be comprehensively discussed with younger patients with a severe curvature. Disclosure: Work supported by industry: no.